COLORISTIC TONAL AND HARMONIC COMPOSITIONAL TECHNIQUES IN ZOLTÁN GÁRDONYI’S CHORAL WORKS FOR ORGAN - IMRE, János Zsolt (Studia Universitatis Babes-Bolyai Musica, 2023)
The topic of this paper is an analysis of two choral works for organ by Zoltán Gárdonyi. The purpose of this work is to reveal the compositional methods and tools used to create coloristic and fascinating tonal and harmonic movements in those two choral works. Alongside, how he crafts his works based on cantus firmus melodies and creates the organ chorals.